Optimization of basic chemistry learning: Validation of STEM-based problem-based learning materials for chemical equilibrium - Mariliaty, Nani; Suhery, Tatang (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: The objective of this study is to create Basic Chemistry learning materials focused on the topic of Chemical Equilibrium using a Science, Technology, Engineering and Math (STEM) Problem-Based Learning approach. Effective learning is necessary to enhance students' understanding of complex chemistry concepts. Method: This study adopts the STEM Problem-Based Learning material development method, utilizing the ADDIE model, which consists of five steps: analysis, design, development, implementation, and evaluation. After the development process, the learning materials were assessed through an expert review stage. Evaluation was conducted to assess the validity of the design, pedagogical validity, and content validity using Aiken's coefficient as an indicator. Results: The expert review evaluation results showed high Aiken's coefficients: 0.98 for design validity, 0.95 for pedagogical validity, and 0.96 for content validity. These findings confirm that the developed learning materials comprehensively meet validity standards. Conclusion: Based on these evaluation results, it can be concluded that the developed Basic Chemistry learning materials, particularly on Chemical Equilibrium using the STEM Problem-Based Learning approach, meet the validity criteria. Therefore, these learning materials are considered suitable for use in the Basic Chemistry learning process. Novelty/Originality of this study: This study integrates the STEM Problem-Based Learning approach into developing Basic Chemistry learning materials, specifically on Chemical Equilibrium. Using the ADDIE model and comprehensive validation, this study presents a new framework for designing learning materials that simultaneously meet design, pedagogical, and content standards.